Insurance Law and the Principle of Indemnity in Light of Ridgecrest NZ Ltd v IAG New Zealand Ltd - Ginders, Kasia (Victoria University of Wellington Law Review, 2016)
When the Supreme Court discussed the principle of indemnity in Ridgecrest NZ Ltd v IAG New Zealand Ltd, it was referred to as "awkward" in the context of a replacement policy. The application of the indemnity principle in the case raises further questions about the nature of the principle in insurance contracts. It is submitted that the indemnity principle is currently enforceable not as a legal test nor as a policy-based presumption; rather, it is applicable mostly because it is presumed the parties intended it to apply. This conclusion draws on both consideration of the rationales and rules of, exceptions to, and law reform concerning the principle. It also draws on analysis of the principle in light of Ridgecrest and two other recent cases following the Christchurch earthquakes that deal with the principle of indemnity.